Information Technology: New Generations 13th International Conference on Information Technology - Latifi, Shahram; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book collects articles presented at the 13th International Conference on Information Technology- New Generations, April, 2016, in Las Vegas, NV USA. It includes over 100 chapters on critical areas of IT including Web Technology, Communications, Security, and Data Mining.
Networking and Wireless Communication -- Security and Privacy in Next Generation Networks -- Information Systems and Internet Technology -- Software Engineering -- High-Performance Computing Architectures -- Agile Software Testing and Development -- Model-Driven Engineering for Cyber-Physical Systems -- Data Mining -- New Trends in Wavelet and Numerical Analysis -- Computer Vision, HCI and Image Processing/Analysis -- Potpourri -- Short Papers.
Keywords: Computer networks .; Data structures (Computer science).; Information theory; Data protection; Computer Communication Networks; Data Structures and Information Theory; Data and Information Security